Perbandingan Keefektivitasan Pemberian Bubur Kacang Hijau dan Sayur Daun Kelor terhadap Peningkatan Produksi ASI pada Ibu Menyusui - Kustini, Eneng Iis; Azizah, Imroatul (Universitas Malahayati, 2025)
ABSTRACT Mothers who do not breastfeed their babies on the first day of breastfeeding are caused by the mother's anxiety and fear about the lack of breast milk production, so that the mother is not sure that she can provide breast milk. One way to ensure that mothers are successful in providing exclusive breast milk is by giving them additional food to prevent a decline in breast milk production. It has been scientifically proven that green beans which contain natural vitamin B complex help improve the health of breastfeeding mothers and help breast milk production. There are vegetables that can increase breast milk production, namely Moringa leaves. Moringa leaves are leaves that contain the flavonoid content in Moringa leaves has been proven for breastfeeding mothers in terms of increasing breast milk production. To determine the comparison of the effectiveness of giving green bean porridge and Moringa leaf vegetables to increase breast milk production in breastfeeding mothers in the Warunggunung Inpatient Health Center UPTD Work Area in 2024. This research is quantitative research using a quasi-experimental design with a pretest-post control group design approach. Sampling used Purposive Random Sampling. The instrument used for data collection was a questionnaire, then the data was analyzed using the Independent T Test. The average score from filling out a questionnaire regarding breast milk production after being given green bean porridge was 7.42, while in the group given Moringa leaf vegetables it was 5.89. It can be seen that the mean value in the group given green bean porridge was greater than the group given Moringa leaf vegetables. This shows that peanut porridge is more effective than giving Moringa leaf vegetables to increase breast milk production in breastfeeding mothers. The results of the Independent Sample T Test obtained a P Value of 0.017 (<0.05), meaning that there was a difference in the effectiveness of giving Green Bean Porridge and Moringa Leaf Vegetables to Increase Breast Milk Production in Breastfeeding Mothers in the Warunggunung Inpatient Health Center UPTD Work Area in 2024. Keywords: Green Bean Porridge, Moringa Leaf Vegetables, Breast Milk Production ABSTRAK Ibu yang tidak menyusui bayinya pada hari pertama menyusui disebabkan oleh kecemasan dan ketakutan ibu akan kurangnya pengeluaran ASI, sehingga ibu tidak yakin bisa memberikan ASI. Salah satu upaya agar ibu berhasil dalam memberikan ASI secara eksklusif yaitu dengan memberikannya tambahan makanan agar tidak terjadinya kemunduran dalam produksi ASI. Telah terbukti secara ilmiah bahwa kacang hijau yang mengandung vitamin B kompleks alami membantu meningkatkan kesehatan ibu menyusui dan membantu produksi ASI. Selain dari kacang hijau, daun kelor merupakan daun yang memiliki kandungan flavonoid yang membeantu untuk ibu menyusui dalam memperbanyak produksi ASI. mengetahui perbandingan keefektivitasan pemberian bubur kacang hijau dan sayur daun kelor terhadap peningkatan produksi ASI pada ibu menyusui di Wilayah Kerja UPTD Puskesmas Rawat Inap Warunggunung Tahun 2024.Penelitian ini merupakan penelitian kuantitatif menggunakan desain quasi eksperimental dengan pendekatan pretes-post control group design. Pengambilan sampel menggunakan Purposive Random Sampling. Instrumen yang digunakan untuk pengumpulan data menggunakan keusioner kemudian data-data tersebut dianalilsis menggunakan uji Independent T Test. Rata-rata skor hasil pengisian kuesioner sesudah diberikan bubur kacang hijau sebesar 7,42, sedangkan pada kelompok yang diberikan sayur daun kelor sebesar 5,89. Telihat bahwa nilai mean pada kelompok yang diberikan bubur kacang hijau lebih besar dari kelompok sayur daun kelor. Ini menunjukkan bubur kacang hijau lebih efektif dibanding dengan pemberian sayur daun kelor untuk meningkatkan produksi ASI pada ibu menyusui. Hasil Uji Independent Sample T Test didapatkan P Value 0,017 (<0,05), artinya terdapat perbedaan Keefektivitasan Pemberian Bubur Kacang Hijau dan Sayur Daun Kelor Terhadap Peningkatan Produksi ASI Pada Ibu Menyusui di Wilayah Kerja UPTD Puskesmas Rawat Inap Warunggunung. Kata Kunci: Bubur Kacang Hijau, Sayur Daun Kelor, Produksi ASI